2021
DOI: 10.3389/fimmu.2021.663586
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing Ivermectin for COVID-19: Molecular Aspects and Therapeutic Possibilities

Abstract: As of January 2021, SARS-CoV-2 has killed over 2 million individuals across the world. As such, there is an urgent need for vaccines and therapeutics to reduce the burden of COVID-19. Several vaccines, including mRNA, vector-based vaccines, and inactivated vaccines, have been approved for emergency use in various countries. However, the slow roll-out of vaccines and insufficient global supply remains a challenge to turn the tide of the pandemic. Moreover, vaccines are important tools for preventing the disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 60 publications
0
28
0
1
Order By: Relevance
“…Other meta-analyses have specifically examined the role of ivermectin for COVID-19 [6,17,18]. One, based on 4 trials and 397 participants, concluded that ivermectin reduced overall mortality and led to a significant clinical improvement compared to the usual therapy, but also highlighted the limitations of these conclusions due to the very low quality of the available evidence [7]. In the other two reviews, overall mortality was the only outcome considered; both studies revealed a significant reduction of the odds of mortality in ivermectin recipients compared to the controls [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Other meta-analyses have specifically examined the role of ivermectin for COVID-19 [6,17,18]. One, based on 4 trials and 397 participants, concluded that ivermectin reduced overall mortality and led to a significant clinical improvement compared to the usual therapy, but also highlighted the limitations of these conclusions due to the very low quality of the available evidence [7]. In the other two reviews, overall mortality was the only outcome considered; both studies revealed a significant reduction of the odds of mortality in ivermectin recipients compared to the controls [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Ruxolitinib and baricitinib target the Janus-Kinase pathway and inhibit cytokine release [ 66 , 67 ]. The other repurposing drugs have miscellaneous effects on the viral pathogenesis and inhibit the viral growth by different mechanisms, for instance, ivermectin inhibits the nuclear transport activity, and statins targets the angiotensin-converting enzyme 2 [ 68 , 69 ]. The remdesivir, the most accepted repurposed drug for the SARS-CoV-2, inhibits the RdRp protein, therefore, inhibits the viral replication [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2020, Caly et al [ 164 ] found that Ivermectin is an inhibitor of SARS-CoV-2 in-vitro and though the mechanism is unknown, it is hypothesized to work by disinhibiting the virus’s evasion tactics from the host immune cells and thus abrogate sufficient viral replication and allow the host to clear it. Another suggested mechanism is the suppression of the production of Interleukin-6 (IL-6) and Tumor Necrosis Factor alpha (TNFα), two major components of the detrimental cytokine storm induced by SARS-CoV-2 [ 165 ].…”
Section: Targeting Covid-19 Therapymentioning
confidence: 99%
“…Both the Food and Drug Administration (FDA) of the United States and European Medicines Agency (EMA) have advised against its use, stating insufficient evidence for any benefit [ 166 ]. It has been highlighted that the required concentration of 5 µM to reach the anti-SARS-CoV-2 action of Ivermectin observed in vitro is fifty-fold higher than the current FDA-approved dosage (200 μg/kg) [ 165 , 166 ]. Hence, this may explain why it was not included in large-scale clinical trials such as the Solidarity trial [ 166 ].…”
Section: Targeting Covid-19 Therapymentioning
confidence: 99%
See 1 more Smart Citation